The Effect of Sustainability Reporting, Corporate Social Responsibility, Profitability on Firm Value in the Consumer Non-Cyclicals Sector Listed on the Indonesia Stock Exchange in 2021-2023 - Mitzy, Sheryl Esfandian Mitzy; Wijaya, Henryanto (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to evaluate the impact of Sustainability Reporting, Corporate Social Responsibility (CSR), and the level of profitability on firm value in the consumer non-cyclicals subsector listed on the Indonesia Stock Exchange during the period 2021 to 2023. To measure profitability, this study uses the Return on Equity (ROE) indicator. The methodology applied is quantitative with a multiple linear regression analysis approach as the main analysis tool. Based on the results obtained, Sustainability Reporting and CSR are proven to have no significant influence on firm value. In contrast, ROE shows a significant positive effect, indicating that companies with a high level of profitability tend to have better company value. This finding underscores that financial performance, particularly profitability, plays a more dominant role in shaping firm value than sustainability reporting or social activities.